Pengembangan Bahan Ajar Materi Perubahan Iklim pada Ekstrakurikuler Sekolah Siaga Bencana di SMP Negeri 1 Wedi - Khoirunisa, Nanda, Siti Azizah Susilawati, S.Si, MP (2017)
The aims of this research is to know, 1) criteria of eaching material, 2) model of development teaching material, and 3) the effectiveness of teaching materials or book on climate change material in extracurricular Sekolah Siaga Bencana. Model of development teaching material adopted design of Borg and Gall. Design of study using one group pretest-posttest design with 25 respondents who participants of extracurricular Sekolah Siaga Bencana in SMP Negeri 1 Wedi. Data analysis techniques used T-test. Differences erstanding on climate change meterial pretest and increased posttest avarage value was 24,8. The average value pretest is 64 increase on posttest become 88,8. The results of the test (T-test) pretest and posttest data indicates significant value 0,000<0,05 so H0 was rejected and H1 accepted that significant differences occurred beetween pretest and posttest result. Teaching material or product developed otherwise used in learning process on extracrricular Sekolah Siaga Bencana. Assement results of product by respondents have value of 4,75 and include on category "GOOD."